2021
DOI: 10.1371/journal.pgen.1009939
|View full text |Cite
|
Sign up to set email alerts
|

An optimal growth law for RNA composition and its partial implementation through ribosomal and tRNA gene locations in bacterial genomes

Abstract: The distribution of cellular resources across bacterial proteins has been quantified through phenomenological growth laws. Here, we describe a complementary bacterial growth law for RNA composition, emerging from optimal cellular resource allocation into ribosomes and ternary complexes. The predicted decline of the tRNA/rRNA ratio with growth rate agrees quantitatively with experimental data. Its regulation appears to be implemented in part through chromosomal localization, as rRNA genes are typically closer t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 69 publications
(157 reference statements)
1
22
0
Order By: Relevance
“…the four genes for tRNA GUU -Asn) did not have identical growth impacts, corroborating previous work suggesting that copies of the same tRNA contribute differently to translation ( Dittmar et al, 2004 ). These differences could potentially arise due to genomic location – prior work shows that tRNA gene expression is correlated with distance from the origin of replication ( Ardell and Kirsebom, 2005 ; Hu and Lercher, 2021 ). However, we did not find a correlation between the fitness impacts of gene deletion and distance from the origin of replication, across copies of the same tRNA isotype or across all tRNA genes ( Figure 2—figure supplement 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…the four genes for tRNA GUU -Asn) did not have identical growth impacts, corroborating previous work suggesting that copies of the same tRNA contribute differently to translation ( Dittmar et al, 2004 ). These differences could potentially arise due to genomic location – prior work shows that tRNA gene expression is correlated with distance from the origin of replication ( Ardell and Kirsebom, 2005 ; Hu and Lercher, 2021 ). However, we did not find a correlation between the fitness impacts of gene deletion and distance from the origin of replication, across copies of the same tRNA isotype or across all tRNA genes ( Figure 2—figure supplement 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to the relative size of the rRNA and tRNA pools specifically, it has been observed repeatedly that the ratio of ternary complexes (charged tRNAs bound to EF-Tu⋅GTP) to ribosomes increases at decreasing steady-state growth rates [see Scott et al, 2014 and references therein]. The growth-rate-dependence of this ratio was faithfully replicated theoretically by computing the minimal sum of ribosome and ternary complex masses (RNA and protein) that would yield the protein production rates characteristic for each growth rate ( Hu and Lercher, 2021 ). Furthermore, the optimal ratio of ternary complexes to ribosomes at different steady-state growth rates was proposed to be hard-wired into the genome of fast-growing bacteria, arising as a direct consequence of the relative location of rRNA and tRNA genes relative to the origin of replication ( Hu and Lercher, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…The growth-rate-dependence of this ratio was faithfully replicated theoretically by computing the minimal sum of ribosome and ternary complex masses (RNA and protein) that would yield the protein production rates characteristic for each growth rate ( Hu and Lercher, 2021 ). Furthermore, the optimal ratio of ternary complexes to ribosomes at different steady-state growth rates was proposed to be hard-wired into the genome of fast-growing bacteria, arising as a direct consequence of the relative location of rRNA and tRNA genes relative to the origin of replication ( Hu and Lercher, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear, however, if these genes contain other useful information, such as information about the optimal growth environment for a given species. Previous studies found that ribosomal genes contain some information about a given organism's optimal growth temperature [13][14][15][16][17][18][19][20][21][22][23] . For instance, thermophilic ribosomal proteins were found to have a higher content of arginine, isoleucine, proline, and tyrosine, and a decreased content of serine and threonine.…”
Section: Introductionmentioning
confidence: 99%
“…However, this correlation was not consistent across species to serve as an accurate predictor of an organism's optimal growth temperature 13,14 . A more promising approach was established by studying the correlation between the optimal growth temperature and the G+C content in rRNA [15][16][17][18][19][20][21][22][23] . For example, an almost linear correlation was observed in 143 microbial genera, where the rRNA G+C content gradually increased from about 45% G+C in psychrophilic bacteria to about 55% G+C in thermophilic bacteria 15 .…”
Section: Introductionmentioning
confidence: 99%